2023
DOI: 10.3390/brainsci13050723
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Formal Music Training and Conflict Control: An ERP Study

Abstract: Music training involves manifolds of sensorimotor processes that tie closely with executive functions, including conflict control. Past studies have found consistent evidence in children of the link between music learning and executive functions. However, the same relationship has not been found in adult populations, and conflict control has yet to be studied in a focused manner. Via the Stroop task and event-related potentials (ERPs), the present study examined the association between musical training and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…Previous studies have demonstrated that individuals with music training typically have higher P3 amplitudes, which reflect their better cognitive abilities (Collins and Koechlin, 2012 ). However, our results showed that the P3 amplitude of the control group was greater than that of the music group, which has also been confirmed by Hao et al ( 2023 ). During their selecting tasks, individuals in the control group put in more cognitive effort, demonstrating that the control group needed more monitoring and inhibitory abilities in order to respond correctly to the switch task.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that individuals with music training typically have higher P3 amplitudes, which reflect their better cognitive abilities (Collins and Koechlin, 2012 ). However, our results showed that the P3 amplitude of the control group was greater than that of the music group, which has also been confirmed by Hao et al ( 2023 ). During their selecting tasks, individuals in the control group put in more cognitive effort, demonstrating that the control group needed more monitoring and inhibitory abilities in order to respond correctly to the switch task.…”
Section: Discussionsupporting
confidence: 91%
“…The self-report tool evaluates differences in musical skills in the general, non-specialist population, and gauges diverse aspects of musical sophistication, including active engagement, perceptual abilities, singing abilities and emotional responses to music. In addition, the number of years of formal training was measured as it has shown associations with performance in Simon ( Slevc et al, 2016 ; Joret et al, 2017 ) and Stroop tasks ( Hao et al, 2023 ). Based on the results of the Gold-MSI, participants were split at the median (Median = 2 years of training, Mean = 3.4 ± 2.2, Range = 0–10 years) into high- (Mean = 5.86 ± 3.5 years of training) and low- (Mean = 0.3 ± 0.4 years of training) musical training groups for subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The self-report tool evaluates differences in musical skills in the general, non-specialist population, and gauges diverse aspects of musical sophistication, including active engagement, perceptual abilities, singing abilities and emotional responses to music. In addition, the number of years of formal training was measured as it has shown associations with performance in Simon (Slevc et al, 2016;Joret et al, 2017) and Stroop tasks (Hao et al, 2023)…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that individuals with lower e ciency in mobilizing inhibitory control resources are more prone to consuming a greater number of calories (Carbine et al, 2017a) The N2 component, characterized by a negative de ection and stimulus reactivity, exhibits a greater amplitude when more con icts are detected (Botvinick et al, 2001;Clayson & Larson, 2013). Individuals with music training have been found to display larger N2 amplitudes (Hao et al, 2023). Moreover, soothing and cheerful music have been shown to regulate negative emotions and reduce N2 amplitude (X.…”
Section: Introductionmentioning
confidence: 99%